Antifungal activities of flower extracts of Inula britannica L. with different solvents - ZHOU Lin; JIAO Bin; GAO Fei; SONG Tian-you; ZHANG Xing (浙江大学学报. 农业与生命科学版)
In order to understand the fungicidal activity of Inula britannica, ethanolic extract of its flowers was separated by different solvents and the activities of different solvent extracts against 13 plant pathogenic fungi were tested in vitro and in vivo. The results showed the extraction rates of petroleum ether, chloroform, ethylacetate and n-butyl alcohol were 34.89%, 8.99%, 8.63% and 22.72%, respectively. Chloroform extract at the concentration of 1.0 mg·mL-1 exhibited strongly fungicidal activities to mycelium growth of the investigated fungi, and the inhibition rates against Phytophthora capsici and Sclerotinia sclerotiorum were 73.77% and 66.25%; the inhibition rates of the ethylacetate extract and n-butyl alcohol extract against P. capsici and S. sclerotiorum were 67.69%, 62.12% and 56.07%, 51.75%, respectively; the inhibition rate of the petroleum ether extract against Botrytis cintrea was 58.70%. With the same application rate as above, the chloroform extract could inhibit the spore germination of Colletotrichum dematium, Fusarium oxysporum on the cotton, Colletotrichum gloeosporioides, Fusarium graminearum and Fusarium oxysporum on the capsicum, and the inhibition rates were 96.00%, 92.44%, 80.43%, 78.45% and 71.84%, respectively; the inhibition rates of ethylacetate extract against six investigated fungi were from 40.86% to 86.42%; spore germination was inhibited markedly in F. oxysporum by petroleum ether extract, and the inhibition rate was 82.52%. The protective and therapeutic efficacies of chloroform extract against B. cinerea were 57.65% and 50.60% (6 d) on the tomato treated at the concentration of 2.0 mg·mL-1, respectively, and its therapeutic efficacy wasn't significantly different with the control fungicide-pyrimethanil at 0.4 mg·mL-1.